2012
DOI: 10.1371/journal.pbio.1001389
|View full text |Cite
|
Sign up to set email alerts
|

3D-SIM Super Resolution Microscopy Reveals a Bead-Like Arrangement for FtsZ and the Division Machinery: Implications for Triggering Cytokinesis

Abstract: Super resolution three-dimensional imaging reveals a new picture of how bacterial cell division proteins localize to the division site, including the formation of dynamic bead-like patterns, and explains how the division ring constricts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
187
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(209 citation statements)
references
References 65 publications
(104 reference statements)
17
187
0
1
Order By: Relevance
“…The midcell percentage (p mid ) of FtsZ-mEos2 remained constant until the Z-ring diameter reached ∼250 nm (Fig. 3F), consistent with previous studies that monitored early stages of Z-ring closure (diameter, >300 nm) (43,51). However, in cells with smaller diameters (<250 nm), p mid decreased significantly (Fig.…”
Section: Constriction Initiation and Progress Does Not Require Z-ringsupporting
confidence: 90%
See 2 more Smart Citations
“…The midcell percentage (p mid ) of FtsZ-mEos2 remained constant until the Z-ring diameter reached ∼250 nm (Fig. 3F), consistent with previous studies that monitored early stages of Z-ring closure (diameter, >300 nm) (43,51). However, in cells with smaller diameters (<250 nm), p mid decreased significantly (Fig.…”
Section: Constriction Initiation and Progress Does Not Require Z-ringsupporting
confidence: 90%
“…We showed that the Z-ring is not a smooth structure but instead comprises clusters of FtsZ protofilaments that loosely associate into a 3D bundle (19,48). This heterogeneous morphology has also been observed with several different fluorescent protein tags (19), in different bacterial species (51)(52)(53)(54), by immuno-superresolution imaging targeting native FtsZ (19,54), by superresolution imaging of FtsZ-binding proteins (19,54), and in an early electron cryotomography (ECT) study (37). Here, we further demonstrate that an FtsZ-GFP fusion colocalizes with native FtsZ in midcell clusters in two-color superresolution imaging using antibodies against native FtsZ and GFP (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Following studies using highresolution fluorescence microscopy techniques revealed that such was the case in many other bacterial species (Strauss et al 2012, Rowlett & Margolin 2014, Jacq et al 2015. It was also hypothesized that GTP-bound FtsZ assemble into straight protofilaments at many nucleation points at the mid-cell and attach themselves to the membrane (Lu et al 2000).…”
Section: :9mentioning
confidence: 98%
“…However, this is technically challenging at present, and image acquisition is slow. The first super-resolution images of the bacterial divisome came from IFM of B. subtilis FtsZ (STED), B. subtilis cells producing FtsZ-GFP as the only copy of FtsZ in the cell (3D-SIM), and Staphylococcus aureus cells producing FtsZ-GFP as a label with native FtsZ present (3D-SIM) [66,68,76]. These studies revealed that FtsZ formed a patchy, discontinuousappearing structure, with clear areas of low fluorescence around the ring circumference.…”
Section: Super-resolution Of the Divisome: Is The Z-ring A Patchy Tormentioning
confidence: 99%